Transgenic plants expressing ω-ACTX-Hv1a and snowdrop lectin (GNA) fusion protein show enhanced resistance to aphids - Nakasu, Erich Y. T.; Edwards, Martin G.; Fitches, Elaine; Gatehouse, John A.; Gatehouse, Angharad M. R. (Frontiers in Plant Science, 2014)
Recombinant fusion proteins containing arthropod toxins have been developed as a new class of biopesticides. The recombinant fusion protein Hv1a/GNA, containing the spider venom toxin w-ACTX-Hv1a linked to snowdrop lectin (GNA) was shown to reduce survival of the peach-potato aphid Myzus persicae when delivered in artificial diet, with survival <10% after 8 days exposure to fusion protein at 1 mg/ml. Although the fusion protein was rapidly degraded by proteases in the insect, Hv1a/GNA oral toxicity to M. persicae was significantly greater than GNA alone. A construct encoding the fusion protein, including the GNA leader sequence, under control of the constitutive CaMV 35S promoter was transformed into Arabidopsis; the resulting plants contained intact fusion protein in leaf tissues at an estimated level of 25.6±4.1 ng/mg FW. Transgenic Arabidopsis expressing Hv1a/GNA induced up to 40% mortality of M. persicae after seven days exposure in detached leaf bioassays, demonstrating that transgenic plants can deliver fusion proteins to aphids. Grain aphids (Sitobion avenae) were more susceptible than M. persicae to the Hv1a/GNA fusion protein in artificial diet bioassays (LC50=0.73 mg/ml after two days against LC50=1.81 mg/ml for M. persicae), as they were not able to hydrolyze the fusion protein as readily as M. persicae. Expression of this fusion protein in suitable host plants for the grain aphid is likely to confer higher levels of resistance than that shown with the M. persicae/Arabidopsis model system.